Phylogeography and demographic history of Atherina presbyter (Pisces: Atherinidae) in the North-eastern Atlantic based on mitochondrial DNA - Francisco, Sara Martins (2012)
A fragment of the mitochondrial control region was used to assess phylogeographic patterns and historical demography of the sand-smelt Atherina presbyter in the North-eastern Atlantic, covering its geographical range. A striking result is the highly marked diVerentiation between the Canary Islands population and western European ones. A genetic structure among European populations of A. presbyter was revealed, with a pattern of isolation-by-distance or a gradient eVect at a scale of hundreds kilometres, an uncommon pattern likely related to the biological and life-history traits of the sand-smelt. The northern European populations present a much lower genetic diversity when compared to southern populations, which is consistent with a recent colonization from southern populations. The results showed signs of Pleistocene signatures, with the population age estimates for the European populations being clearly older than the Last Glacial Maximum (18,000 years bp). Nevertheless, paleotemperature reconstructions show that the sand-smelt could not have inhabited the western European shores during the last glacial phase.